Beyond Aid: A New Metric for Official Development Assistance Post-2015 - Domínguez Martín, Rafael (2013)
The study attempts to respond to the question, “after 2015, what will constitute the idea of ‘beyond aid,’ whose origins were associated with the policy coherence?” After analyzing the new context of fatigue in Official Development Assistance (ODA) and the identity crisis of the aid regime, the various metrics proposed for a redefinition of the concept of ODA after 2015 are addressed. It seems that in no case ODA will be related to the initial idea of policy coherence, but rather to an attempt among the traditional European donors to cover over their failure to fulfill their commitment to 0.7% of GNP and relax criteria with the (entirely uncertain) purpose of attracting providers of South-South assistance cooperation from the big leagues (Brazil, Russia, India, China, South Africa, or BRICS) and the secondary leagues (Indonesia, Malaysia, Thailand, Turkey, Mexico, Chile, Colombia, or Peru) to the Development Assistance Committee.